Reduction of Dimension Out Defects in Electronic Products Using Process Control Methods with Fish Diagrams and FMEA - Hartono, Hartono; Pratama, Mohammad Rafi; Hanafi, Muhammad Imam; Nurali, Muhammad; Prastyo, Yudi (Lentera Ilmu Nusantara, 2025)
This research was conducted at PT. XYZ, a metal stamping company, to identify and mitigate dimension out problems. The research took place from August to October and used problem-solving methods such as Root Cause Analysis (RCA), Statistical Process Control (SPC), Fishbone Diagram, and Failure Modes and Effects Analysis (FMEA). The main problems identified were the inconsistency of operators in working and the frequent fluctuations of the machines used, which had a significant impact on the final production output. The SPC method is used to monitor process variations and identify deviation patterns. Fishbone Diagram helps in identifying the underlying causative factors of this problem, while RCA is used to dig deeper into the root causes. FMEA is applied to assess the risks associated with these variations and determine the priority of corrective actions. The results of the analysis show that variations in operator performance and engine turnover are often the main factors causing dimensional problems. Corrective measures implemented include operator retraining to improve work consistency, implementation of stricter standard procedures, and machine maintenance schedules to reduce the frequency of engine changes. The implementation of this action has succeeded in significantly reducing the frequency of dimension out and increasing the stability of the production process. This study concludes that the use of a structured and comprehensive approach in identifying and overcoming dimension out problems can improve product quality and production efficiency at PT. XYZ. Recommendations for continuous improvement are also recommended to ensure that the process remains stable in the long term and from the data collected, it can be seen that the largest contributor rejection is dimension out, namely the size of the product exceeding the specifications. If this size excess is too large to exceed the existing tolerances, it will greatly affect the yield in the assembly process. If found in customers , it will have a fatal effect on customer trust in the quality of the products produced. This can have an impact on the company's business interests.